The other side of screening: predictors of treatment and follow-up for anal precancers in a large health system. (1st November 2021) - Silvera, Richard; Martinson, Tyler; Gaisa, Michael M.; Liu, Yuxin; Deshmukh, Ashish A.; Sigel, Keith
Abstract : Background: Anal cancer disproportionately affects people with HIV (PWH). High-grade squamous intraepithelial lesions (HSIL) are cancer precursors and treating them might prevent anal cancer. Data on adherence to HSIL treatment and surveillance is limited but needed to identify deficiencies of screening strategies. Methods: We collected data on high-resolution anoscopy (HRA) attendance and outcomes from 2009 to 2019 in a large urban anal cancer-screening program. Patients with an initial HSIL diagnosis were followed for return for HSIL electrocautery ablation within 6 months of index HSIL diagnosis, and follow-up HRA within 18 months of index HSIL diagnosis. We also evaluated predictors of these outcomes in univariable and multivariable analyses. Results: One thousand one hundred and seventy-nine unique patients with an anal HSIL diagnosis were identified and 684 (58%) returned for electrocautery ablation. Of those treated, only 174 (25%) and only 9% of untreated HSIL patients (47 of 495) underwent surveillance HRA within 18 months of index HSIL diagnosis. In multivariable analyses, black patients and PWH regardless of virologic control were less likely to undergo HSIL ablation within 6 months of HSIL diagnosis whereas patients with commercial insurance were more likely to be treated within 6 months of diagnosis. Among treated HSIL patients, PWH with viremia had a lower likelihood of engaging in post-treatment surveillance within 18 months of HSIL diagnosis. Discussion: Even in large specialized anal cancer screening programs adherence to HSIL treatment and surveillance is low. Psychosocial and economic determinants of health may impact retention in care. Addressing both personal and structural barriers to patient engagement may improve the effectiveness of anal cancer screening.